Did changing work and family demands during COVID-19 (de)motivate academic parents to craft sustainable careers? - Kilic, Eren; Cetin-Kilic, Nergiz; Tatar, Berivan (Ios Press, 2024)
BACKGROUND: Covid-19 has introduced many contextual changes into individuals' work and family lives, affecting their career sustainability. Although previous studies have provided evidence for these changes, little is known about how changing contextual demands (de)motivated them to take proactive initiatives for crafting sustainable careers. OBJECTIVE: This study aims to explore how changing work and family demands of academic parents during Covid-19 affected their career sustainability indicators and career initiatives regarding health, happiness, and productivity. METHODS: Data were collected through semi-structured interviews with 21 academic parents during the post-lockdown period of Covid-19 in Turkey. We analyzed the qualitative data by using content analysis via MAXQDA software. RESULTS: Results revealed differing career sustainability experiences and initiatives regarding gender roles, career stage, and work/family demands and resources. Notably, women academics with higher contextual demands and lower contextual resources and early-career academics reported relatively adverse experiences concerning their health, happiness, and productivity. Besides, even though early-career academics faced problems with sustaining their career development, they were relatively more oriented to engage in career initiatives, such as reorganizing developmental needs, improving career skills, and seeking career support and guidance. CONCLUSIONS: This study sheds light on the context, time, and person aspects of sustainable careers during Covid-19. Moreover, the study represents one of the first investigations into the proactive initiatives for crafting sustainable careers during the pandemic and provides a deeper insight into the (de)motivators for career proactivity.
Keywords: Covid-19; career choice; sustainable development; parents; work-family balance; academic performance; gender role; qualitative research